Physiological monitoring of stress and major depression: A review of the current monitoring techniques and considerations for the future. (May 2022) - Ahmed, Tashfia; Qassem, Meha; Kyriacou, Panicos A.
Abstract: Mental illnesses such as clinical and major depression have taken its toll on the global burden of disease, leading to unprecedented cases worldwide. Commonly, the diagnostic and prognostic procedures for such mental illnesses comprise of qualitative and subjective measures of stress, which can often lead to misdiagnosis and improper treatment courses. In recent years, the quantification and objectification of stress has given rise to an alternative approach to dated practices in the psychophysiological evaluation of stressed and depressed individuals. This has been made possible in recent years through the advancements in heart rate variability (HRV), electrodermal activity (EDA) and electroencephalography (EEG). This review comprehensively evaluates the current state-of-the-art technology in these fields and their applications within mental health monitoring and diagnosis. We have seen an escalation in the application of multimodal approaches towards stress monitoring for major depression, further emphasizing the need for technological advancements in this space, for the betterment of the global burden of disease.